Performance, Gastrointestinal Tract Traits, and Cecal Short Chain Fatty Acid Concentration of Two Commercial Broiler Strains Fed With Processed Wheat Straw - A Samadi; S Mirzaie Goudarzi; AA Saki; A Ahmadi (Brazilian Journal of Poultry Science)
ABSTRACT The aim of this work was to study the growth performance, gastrointestinal tract traits, and cecal short chain fatty acid (SCFA) concentration in response to insoluble fiber in two broiler strains from 0 to 42 days of age. The experiment had a completely randomized design (CRD) with four treatments and four replicates (17 birds per replicate) arranged as a 2 × 2 factorial with two broiler strains (Ross 308 vs. Cobb 500) and two processed wheat straw (PWS) levels (0 vs. 3%). Average daily feed intake (ADFI) (p<0.0001), and body weight gain (BWG) (p=0.0025) were greater and feed conversion ratio (FCR) (p<0.0001) was poorer in Cobb than in Ross birds from 0 to 21 days of age. In contrast, higher BWG was observed in the Ross birds from 22 to 42 days of age (p=0.0448). Processed wheat straw did not affect performance from 0 to 21 days; however, BWG was lower from 22 to 42 days of age (p=0.0098). The concentration of acetate (p<0.0001), propionate (p<0.0001) and butyrate (p=0.0063) in the cecum was higher in Ross birds fed with PWS. Overall, broiler strains responded similarly to dietary insoluble fiber. Moreover, the inclusion of PWS had no negative effect on carcass yield at marketing weight, while also improving gastrointestinal tract development and cecal SCFA concentration.